PEER TUTOR IN LESSON STUDY - Kurniati, Kurniati; Wulandari, Fitri (Smart, 2019)
This study aims to describe process implementation of peer tutor - in lesson study  especially writing class. This research is qualitative research conducted on even semester students of the English study program at STKIP Muhammadiyah Pringsewu, Lampung. The data collection technique uses questionnaires and documentation. Data analysis uses Interactive Model which consists of collection, reduction, display, and conclusion drawing data. The result research was students feel learning process given organized and not only process but also the tasks were given structure. It helps students in understanding and reached the purpose of learning easily. Keywords: peer tutor, lesson study, chapter design.